PERBANDINGAN TINGKAT KEDISIPLINAN SISWA YANG MENGIKUTI DAN YANG TIDAK MENGIKUTI EKSTRAKURIKULER PRAMUKA DALAM PEMBELAJARAN DI SEKOLAH MTS NEGERI 1 PELALAWAN - Rorin Adriansyah; Aref Vai; Muhammad Imam Rahmatullah (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This comparative study aims to evaluate the difference in the level of learning discipline between class VIII students who follow and do not follow extracurricular Scouting at MTs Negeri 1 Pelalawan. Data were collected through a 31-item questionnaire that had been tested for validity and reliability, then analyzed with normality, homogeneity, and independent t-tests. The results showed that 93% of Scout participants and 90% of non-participants were in the high discipline category, while the rest were in the medium category; there were no students in the low category. The t-test yielded a calculated t value of 3.532 > t table 1.999 (α = 0.05), indicating a significant difference between the two groups. This finding confirms that participation in extracurricular Scouting contributes to improving students' learning discipline, although strict school rules also play an important role.